2002
DOI: 10.1097/00000542-200211000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alloantigens and Storage-associated Factors on Stimulated Cytokine Response in an In Vitro  Model of Blood Transfusion

Abstract: These data suggest that banked whole blood has an immunosuppressive effect that is largely attributable to storage-dependent factors. These factors are partially removed by prestorage leukodepletion, while the contribution of alloantigens is of minor significance. Immunosuppressive effects are least apparent with leukodepleted erythrocytes, suggesting that the presence of plasma during storage is required for the immunosuppressive effect to develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 37 publications
3
54
2
Order By: Relevance
“…In addition, in vitro allogeneic PRBC transfusion appears to have the potential to promote polymorphonuclear cell-mediated cytotoxicity and to suppress neutrophil locomotion (16) and apoptosis (17). Our findings of significant increases in proinflammatory cytokines after transfusion are in keeping with both in vitro evidence for induction of pro-and anti-inflammatory cytokines following PRBC exposure (18,19) and adult in vivo data (20). Specifically, PRBC transfusion has been demonstrated to result in significant increases in TNF-α (19) and IL-8 (21).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, in vitro allogeneic PRBC transfusion appears to have the potential to promote polymorphonuclear cell-mediated cytotoxicity and to suppress neutrophil locomotion (16) and apoptosis (17). Our findings of significant increases in proinflammatory cytokines after transfusion are in keeping with both in vitro evidence for induction of pro-and anti-inflammatory cytokines following PRBC exposure (18,19) and adult in vivo data (20). Specifically, PRBC transfusion has been demonstrated to result in significant increases in TNF-α (19) and IL-8 (21).…”
Section: Discussionsupporting
confidence: 83%
“…Group H received allogeneic blood transfusion; Group A received autologous whole blood transfusion. plasma components (Claas et al, 2001;Biedler et al, 2002). Patients with documented recurrence and metastasis of cancer at the time of blood drawing had the lower T cell counts of many of those studied (Kuss et al, 2004).…”
Section: ) Cd3mentioning
confidence: 99%
“…Consequently, postoperative blood transfusions are common [9]. However, because of the well-documented risks of ABTs, such as transfusion-associated infections or immunomodulatory effects [2], a reduction in the use of ABT would be a great improvement. Although some authors reported the use of autologous retransfusion systems as a good opportunity to reduce perioperative blood loss [5,26,34,36], there is no consensus regarding whether retransfusion systems also can reduce the use of postoperative ABTs.…”
Section: Discussionmentioning
confidence: 99%
“…This work was performed at Department of Orthopaedic Surgery, Academic Teaching Hospital, Medical University of Innsbruck, Feldkirch, Austria. approximately two units [9]. Because of the inherent risks [10,33] such as transfusion-associated infections and immunomodulation [2] and economic considerations, one common goal in orthopaedic surgery is to reduce the need for allogenic blood transfusions (ABTs) through perioperative blood management [28]. Some studies support measures for reducing blood loss, which include preoperative blood donation [41], correction of preoperative anemia [37], pharmacologic agents such as tranexamic acid injection [29], and autologous retransfusion systems [5,8,26,34,36,43].…”
Section: Introductionmentioning
confidence: 99%